A hoist to the heavens [space elevators]. - Edwards, B.C (IEEE spectrum)
This paper discusses the possibility of using space elevators as an alternative to rocket boosters for space exploration. With the advent of carbon nanotube composites, the space elevator concept has fast been gaining mainstream acceptance. With a space elevator providing cheap, easy, low-risk access to space, people's lives on Earth could be immeasurably enhanced as the wealth of the solar system is brought to their door.